PENGARUH LATIHAN JALAN TANDEM PADA LANJUT USIA DENGAN RIWAYAT RISIKO JATUH - Gazy Arya Septiriawan; Dinasti Pudang Binoriang (Jurnal Riset Daerah, 2024)
Elderly is someone who enters the age of 60-74 years. In this phase a person will experience a decrease in function, one of which is a decrease in physical function which will cause the elderly to be at risk of experiencing fall risk incidents. Prevention of the risk of falling is one of them with tandem walking. To see the effectiveness of tandem walking in the elderly in maintaining balance so as to reduce the risk of falls. This research uses descriptive case study method. The results of the tandem walking intervention before and after obtained differences, namely at the first meeting the elderly could not focus their eyes forward and still had difficulty maintaining body balance, while at the second meeting the elderly could focus their eyes forward and could maintain body balance. The results showed that tandem walking had an effect on the balance of the elderly.